Answer:
A
Step-by-step explanation:
Answer:
Step-by-step explanation:
36 : 3 = 12
12 : 3 = 4
...
4/3 : 3 = 4/
Option A: >
Solution:
Given a triangle GHJ.
The line GH is perpendicular to line HJ.
This means the triangle is a right angled triangle.
In ΔGHJ, GH is the base of the triangle and
HJ is a height of the triangle.
Then the third side must be the hypotenuse of the right triangle.
We know that by the Pythagoras theorem,
![(\text {Hypotenuse})^2=(\text{Base})^2+(\text{Height})^2](https://tex.z-dn.net/?f=%28%5Ctext%20%7BHypotenuse%7D%29%5E2%3D%28%5Ctext%7BBase%7D%29%5E2%2B%28%5Ctext%7BHeight%7D%29%5E2)
![(\text {GJ})^2=(\text {GH})^2+(\text {HJ})^2](https://tex.z-dn.net/?f=%28%5Ctext%20%7BGJ%7D%29%5E2%3D%28%5Ctext%20%7BGH%7D%29%5E2%2B%28%5Ctext%20%7BHJ%7D%29%5E2)
This clearly shows that the hypotenuse is greater than the height.
⇒ GJ > HJ
Option A: > is the correct answer.
If line GH is perpendicular to line HJ, then GJ is > HJ.